A study on perception and acceptance on the goods service tax (GST) implementation among staffs of Kementerian Perdangangan Dalam Negeri, Koperasi dan Kepenggunaan (KPDNKK), Kuching Sarawak / Jarry Jabut - Jabut, Jarry (2015)
This research paper would be related with my training place which is Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan Sarawak (KPDNKK). The research paper will cover their perceptions acceptance on the Goods and Services Tax implementation which be held soon. The organization is powered by 79 staffs in total for the Kuching branch and around 170 staffs for the Sarawak regions. In the Sarawak region the KPDNKK had their branch at places like Kuching itself, Sri Aman, Betong, Sarikei, Sibu, Bintulu, Kapit and Miri.